RİSK ODAKLI VERGİ DENETİMİNDE ELEKTRONİK UYGULAMALAR ÜZERİNE BİR DEĞERLENDİRME. - SERÇEMELİ, Murat (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2019)
With globalization, trade has moved across borders, electronic commerce has become widespread and the structure of enterprises and accounting tools that used have changed. In terms of accounting transactions, former manual transactions were completely replaced by computer programs, while tax-related transactions became executable electronically. Thus, it became possible for taxpayers to carry out their transactions quickly and safely without going to the tax office. One of the most important risks in terms of taxation is the failure of taxpayers to fully and accurately fulfill their tax debts. In order to prevent this risk, it is very important to use today's technological facilities in the audit. The aim of this study is to evaluate the progress of electronic applications used in tax auditing in recent years. For this purpose, first of all, tax risk and compliance were mentioned and then, risk-focused electronic applications were explained and the stages reached in terms of tax were supported with current data. As a result of the research, it has been stated that the increase in tax collection power with electronic applications, the fight against the informal economy and the right to tax justice will provide very positive gains.